2006
DOI: 10.1038/sj.emboj.7601262
|View full text |Cite
|
Sign up to set email alerts
|

TOR regulates late steps of ribosome maturation in the nucleoplasm via Nog1 in response to nutrients

Abstract: The protein kinase TOR (target of rapamycin) controls several steps of ribosome biogenesis, including gene expression of rRNA and ribosomal proteins, and processing of the 35S rRNA precursor, in the budding yeast Saccharomyces cerevisiae. Here we show that TOR also regulates late stages of ribosome maturation in the nucleoplasm via the nuclear GTP‐binding protein Nog1. Nog1 formed a complex that included 60S ribosomal proteins and pre‐ribosomal proteins Nop7 and Rlp24. The Nog1 complex shuttled between the nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 62 publications
0
59
0
Order By: Relevance
“…We demonstrated that TORC1 basic functions are conserved in T brucei. Cells with reduced levels of TbTOR1 showed disperse nucleolar localization of RNA pol I, protein synthesis inhibition, and reduced cell size, as previously shown for other eukaryotes (22)(23)(24).…”
Section: Discussionmentioning
confidence: 51%
“…We demonstrated that TORC1 basic functions are conserved in T brucei. Cells with reduced levels of TbTOR1 showed disperse nucleolar localization of RNA pol I, protein synthesis inhibition, and reduced cell size, as previously shown for other eukaryotes (22)(23)(24).…”
Section: Discussionmentioning
confidence: 51%
“…The finding that TOR signaling affects yeast Nog1p and Nog2p suggests a similar link may exist between TOR signaling and Drosophila NS1. Conversely, inactivation of TOR kinase did not enhance nucleolar retention of the permuted GTPase Nug1p, or that of Bsm1, the nuclear and nucleolar factor required for 40S subunit assembly (Honma et al, 2006). Our future efforts will test the hypothesis that TOR signaling regulates ribosome biosynthesis and/or nuclear export by modulating NS1 activity either directly or indirectly.…”
Section: Possible Links Between Nucleostemin and Stress Responsementioning
confidence: 99%
“…A block in TOR signaling by either nutrient starvation or rapamycin treatment entrapped Nog1p and its associated proteins within nucleoli. Honma et al (2006) concluded that TOR signaling is necessary for the release of the Nog1p complex from the nucleolus perhaps after participating in a relatively early step in 60S subunit assembly. Interestingly, another yeast nuclear and nucleolar GTPase, Nog2p, also accumulated within nucleoli when TOR was inactivated, thus supporting the notion that activated TOR kinase regulates ribosome maturation and export.…”
Section: Possible Links Between Nucleostemin and Stress Responsementioning
confidence: 99%
See 1 more Smart Citation
“…For example, the nop7-1 mutation is synthetically lethal with specific mutant alleles of DRS1, a putative DEAD box helicase necessary for 60S subunit assembly (Adams et al, 2002), and overexpression of DRS1 suppresses certain nop7 mutants (L. Tang, unpublished data). Overexpression of NOP7 suppresses the thermosensitive growth defects of certain mutations in ribosome assembly factor Nog1 (Honma et al, 2006). More experiments need to be done to discover proteins that physically associate with the Nop7-subcomplex within nascent ribosomes.…”
Section: Roles For Domains Other Than Interactions Within the Nop7-sumentioning
confidence: 99%